Development and design of the first structured clinic-based program in lower resource settings to transition emerging adults with type 1 diabetes from pediatric to adult care - Angelica Cristello Sarteau; Ariba Peerzada; Alpesh Goyal; Pradeep A. Praveen; Nikhil Tandon (Public Library of Science (PLoS), 2022)
Introduction Type 1 diabetes (T1D) is increasing in young people worldwide and more children in resource limited settings are living into adulthood. There is a need for rigorous testing and reporting of evidence-based and stakeholder-informed strategies that transition individuals with T1D from pediatric to adult care. We present the development of and design of the first structured transition program in Delhi, India, to inform similar efforts in India and resource limited settings. Methods The intervention development team included clinicians and researchers with expertise in T1D and the implementation context. To select intervention outcomes, establish intervention targets, and design session modules, we drew upon formative research conducted at prospective intervention implementation sites, consensus guidelines, and previous care transition and behavior change research conducted in developed settings. We used the Template for Intervention Description and Replication and GUIDance for the rEporting of intervention Development checklists to report the intervention and development process. Results The 15-month program ("PATHWAY") includes five quarterly ~30 minute sessions delivered predominantly by diabetes educators at pediatric and adult clinics, which coincide with routine care visits. Primary program components include educational and behavioral sessions that address psychosocial drivers of clinic attendance and self-management, diabetes educators as transition coordinators and counselors, and a one-year "overlap period" of alternating visits between pediatric and adult providers. Conclusions We followed a systematic and transparent process to develop PATHWAY, which facilitated rich description of intervention context, guiding principles, targets, and components. Dependence on previously published program examples to design PATHWAY may have introduced challenges for program feasibility and effectiveness, underscoring the importance of input gathering from prospective intervention actors at multiple points in the development process. This detailed report in combination with future evaluations of PATHWAY support efforts to increase rigorous development and testing of strategies to improve outcomes among emerging adults with T1D.